Robust Audio Watermarking using Improved DWT-SVD approach - Patel, Krunalkumar N; Shah, Dipti B (International Journal of Computer Sciences and Engineering, 2025)
Digital watermarking is the technique with the use of that owner’s copyright information can be embedded into the original media either it is in the form of an image, audio or video. It is an essential to maintain the ownership for digital media in sharing of the information. For this audio watermarking is one of the most likely medium to maintain the robustness as well as imperceptibility against the piracy, malicious attacks, and various transformation operations. Though there are some challenges to achieve this results, in this paper, our proposed audio watermarking technique is used to improve the robustness, imperceptibility and accuracy of the information with security. For robustness, in our proposed work we are using synchronized secret key concept and two important transformation methods used are DWT (Discreet Wavelet Transformation) up to 2-level in which the modifications are done in low frequency sub-band and SVD (Singular value Decomposition), so that original audio file does not have any impact of watermark bits to get the better performance. Also, there are more efficient results are presented as per robustness value calculated in this paper with compare to previous work done.